C-5 Epimerisation of d-Mannopyranosyl Fluorides: The Influence of Anomeric Configuration on Radical Reactivity - See, Nicholas W.; Pierens, Gregory K.; Krenske, Elizabeth H.; Ferro, Vito (Synthesis, 2023)
The fluorine-directing effect has so far been exploited to provide short and efficient synthetic routes to rare l-ido sugars. However, the importance of anomeric configuration to its success has remained experimentally unverified. We now report on the synthesis of α- and β-configured per-O-benzoylated mannopyranosyl fluorides and initially show that their reactivity towards photo-bromination is strongly dependent on the anomeric configuration. The stereochemical basis of the fluorine-directing effect is then validated by revealing the striking difference in stereoselectivity observed for the free-radical reductions of the isolated 5-C-bromo sugars. This work importantly provides a synthetic route to a donor-functionalised derivative of l-gulose and reveals new insights into the behaviour of glycosyl radicals.
Keywords: glycosyl radicals; l-hexoses; photochemistry; halides; rearrangements